2022
DOI: 10.34172/joddd.2022.008
|View full text |Cite
|
Sign up to set email alerts
|

Visual perception of repaired cleft lip scarring face associated with different malocclusions via eye-tracking

Abstract: Background. This study aimed to evaluate the visual facial perception in response to scars associated with repaired cleft lip (CL) on a male adolescent patient, as assessed via eye-tracking. Methods. Index of orthodontic treatment need (IOTN) malocclusions, grades 1, 5, and 8 were added to the frontal view facial image of an adolescent male model showing asymmetries of the nose and upper lip after CL surgery using the software Photoshop CS5® software. The eye movements of 91 laypeople observers were tracked by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Only two studies 21,27 used eyetracking glasses rather than screen-based eye-trackers. Chin-rests were used less than half of the time [six studies used chin-rests, 16,[22][23][24]26,30 eight studies did not use chinrests, 15,[17][18][19][20]25,28,29 and two were not applicable (glasses) 21,27 ]. The distance to the screen ranged from 50 to 75 cm; however, this can be dictated by the model of eye-tracker.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only two studies 21,27 used eyetracking glasses rather than screen-based eye-trackers. Chin-rests were used less than half of the time [six studies used chin-rests, 16,[22][23][24]26,30 eight studies did not use chinrests, 15,[17][18][19][20]25,28,29 and two were not applicable (glasses) 21,27 ]. The distance to the screen ranged from 50 to 75 cm; however, this can be dictated by the model of eye-tracker.…”
Section: Resultsmentioning
confidence: 99%
“…15,17,21,23,24,[26][27][28][29][30] Only eight (50%) studies 19,20,[22][23][24][25][26]29 reported time to first fixation 26,29 (time it took the participant to gaze at target AOI) or initial attention capture 19,20,[22][23][24][25] (first AOI participant gazed at upon stimulus display) data. Three studies 15,25,29 (18.8%) reported fixation sequence/scanpath data (path the eyes moved in while viewing the image) and six 15,18,20,26,27,29 (37.5%) displayed heatmaps of fixations as figures within their articles. Detailed information regarding AOI location of fixations, AOI location of initial interest capture and scanpaths as well as further information about data reporting can be found in Supplemental Digital Content 2 (http:// links.lww.com/PRSGO/C567).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, gaze tracking has been widely used to assess facial perception, including in cases of facial deformities. (Guimaraes et al, 2022) In view of the above findings, the present study aimed to evaluate the time of instagram usage in the attractiveness evaluation of the facial silhouettes of patients who had undergone orthognathic surgery and rhinoplasty. For the present study, the null hypothesis is that there is no difference in attractiveness perception of individuals on silhouette images during the initial, post-orthognathic, and final orthognathic and rhinoplasty periods regardless of instagram usage time.…”
Section: Introductionmentioning
confidence: 99%